2020
DOI: 10.1101/2020.03.08.982447
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assembly Mechanism of Mucin and von Willebrand Factor Polymers

Abstract: The respiratory and intestinal tracts are exposed to physical and biological hazards accompanying the intake of air and food. Likewise, the vasculature is threatened by inflammation and trauma. Mucin glycoproteins and the related von Willebrand factor (VWF) guard the vulnerable cell layers in these diverse systems. Colon mucins additionally house and feed the gut microbiome. Here we present an integrated structural analysis of multimerized intestinal mucin MUC2. Our findings reveal the shared mechanism by whic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(65 citation statements)
references
References 47 publications
1
64
0
Order By: Relevance
“…While often considered to be a physical barrier, mucus is actually an active biological barrier that crosslinks viruses and bacteria to mucins, a group of highly glycosylated proteins that are secreted to our mucosal barriers where they self-assemble into long polymers(23). Mucin glycans mimic cell surface glycosylation and by acting as a decoy for viral lectins trap viral particles, which are then transported out of airways by mucociliary clearance(24).…”
Section: Discussionmentioning
confidence: 99%
“…While often considered to be a physical barrier, mucus is actually an active biological barrier that crosslinks viruses and bacteria to mucins, a group of highly glycosylated proteins that are secreted to our mucosal barriers where they self-assemble into long polymers(23). Mucin glycans mimic cell surface glycosylation and by acting as a decoy for viral lectins trap viral particles, which are then transported out of airways by mucociliary clearance(24).…”
Section: Discussionmentioning
confidence: 99%
“…While often considered to be a physical barrier, mucus is actually an active biological barrier that crosslinks viruses and bacteria to mucins, a group of highly glycosylated proteins that are secreted to our mucosal barriers where they selfassemble into long polymers (23). Mucin glycans mimic cell surface glycosylation and, by acting as a decoy for viral lectins, trap viral particles, which are then transported out of airways by mucociliary clearance (24).…”
Section: Figure 2 |mentioning
confidence: 99%
“…Biophysical and single particle EM analysis proposed that the MUC2 mucin is packaged as concatenated polygonal rings, with the mucindomains projecting perpendicular from the base of the rings as parallel rods in a calcium and pH-dependent manner within secretory granules 16 . However, an alternative model suggests that MUC2 complexes exist as linear polymers 24 that are also calcium and pH dependent. Previous studies utilizing single particle EM analysis also identified calcium-mediated cross-links in the VWD-3 domain of MUC5B that could mediate stacking and condensation of the mucin into a round disc-like structure around a central node 25,26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Within the mammalian digestive tract, the predominant intestinal mucin MUC2, is thought to undergo a regulated unfolding process during secretion that results in the formation of a hydrated layer that expands to line and protect epithelial cells 15,21,22 . In vitro studies using N-terminal portions of MUC2 suggest that pH-dependent interactions regulate the formation of supramolecular MUC2 structures 16,23,24 . Based on these in vitro studies, one model suggests that C-terminal disulfide bonding along with Ca 2+ -dependent charge shielding may result in the compaction of MUC2 complexes into stack rings within secretory granules 16 , while an alternative model suggests that MUC2 complexes exist as linear polymers 24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation